Effect of inoculation methods of Azospirillum brasilense on growth and yield of lettuce in the hydroponic system - Hai Chau, Mai; Van Hung, Vu (Journal of Forestry Science and Technology, 2023)
Lettuce (Lactuca sativa L.) is one of the most popular and economically critically leafy vegetable crops in the world. Nevertheless, the existing studies offered information limited on the Azospirillum brasilense eﬀects in this research system makes it necessary to verify the best method of inoculation for these bacteria. Currently, a variety of techniques for producing Lettuce have been investigated, including soilless aeroponic, hydroponic, and deep-water culture systems. Therefore, this study aimed to verify the beneficial eﬀects of inoculation methods of A. brasilense on plant growth and nutrition of two lettuce cultivars grown in the hydroponic system. The study was conducted in a greenhouse with 30% shading at Vietnam National University of Forestry – Dong Nai campus, Trang Bom district, Dong Nai province. A randomized block design with three replicates in a 4 × 2 factorial scheme was used. Four A. brasilense inoculation methods (non-inoculated, foliar application, nutrient solution, and nutrient solution + foliar application) and two lettuce cultivars were evaluated. All inoculation methods improved plant height, shoot fresh and dry mass, fresh leaf yield, and accumulation of potassium, calcium, phosphorus, iron, manganese, and copper. Inoculation via nutrient solution + foliar application of A. brasilense is the most suitable for hydroponic lettuce GR-607 cultivation because it provides greater fresh leaf yield. All inoculation methods increased leaf yield in hydroponic lettuce.